The Influence of Principal's Motivation, Communication, and Parental Participation on Elementary School Teachers’ Performance - Hardiansyah, Framz; Zainuddin, Zainuddin (Al Ibtida: Jurnal Pendidikan Guru MI, 2022)
AbstractThis research was motivated by the collaboration between the principal, teachers, and employees to produce quality education. The purpose of this study was to determine the principal's motivation, communication, and parental participation factors, which together influence the job satisfaction of teachers in elementary schools, and which variables are the most dominant in influencing teachers’ performance. This study uses an explanatory research type with three independent variables: principals (X1), communication (X2), and parent participation (X3), and one dependent variable, namely the performance of teachers (Y). The results of hypothesis testing are calculated as follows: (a) Variable X1 is 0.137 with a probability of 0.105. Because tcount > ttable (1.70 > 0.483) and the level of significance t > 5 % (0.835 > 0.05), variable X1 affects the dependent variable (Y); (b) Variable X2 is 0.227 with a probability of 0.281. Because tcount < ttable (1.70 > 1.020) and the level of significance t > 0.5 % (0.320 > 0.05), the variable (X2) affects the dependent variable (Y); and (c) Variable X3 is 0.267 with a probability of 0.226. Because tcount < ttable (1.70 > 0.750) and the significance level of t > 0.5 % (0.462 > 0.05), the variable (X3) has some influence on the dependent variable (Y). The results of hypothesis testing indicate that the dominant variable is (X2) of 0.227 with a probability of 0.281.Keywords: principal's motivation, communication, parent participation, teachers’ performance.AbstrakPenelitian ini dilatarbelakangi oleh kerjasama antara kepala sekolah dengan guru dan karyawannya dapat menghasilkan mutu pendidikan yang berkualitas. Tujuan Penelitian ini adalah untuk mengetahui faktor motivasi kepala sekolah, komunikasi, dan partisipasi orang tua secara bersama-sama berpengaruh terhadap kepuasan kerja guru di sekolah dasar serta Variabel mana yang paling dominan (motivasi kepala sekolah (X1), komunikasi (X2), Partisipasi Orangtua (X3)) yang mempengaruhi kinerja guru (Y). Penelitian ini menggunakan jenis penelitian Explanatori, dengan variabel bebas yaitu (X1), (X2), (X3) mempunyai pengaruh terhadap (Y). Hasil pengujian hipotesis didapat: (a) Variabel X1 sebesar 0,137 dengan probabilitas 0,105. Karena thitung > ttabel (1.70 > 0.483) serta tingkat signifikansi t > 5 % (0.835 > 0.05), maka variabel X1 berpengaruh terhadap variabel (Y). (b) Variabel X2 sebesar 0.227 dengan probabilitas 0.281. Karena thitung < ttabel (1.70 > 1.020) serta tingkat signifikansi t > 0.5 % (0.320 > 0.05), maka variabel (X2) berpengaruh terhadap variabel (Y). (c) Variabel X3 sebesar 0.267 dengan probabilitas 0.226. Karena thitung < ttabel (1.70 > 0.750) serta tingkat signifikansi t > 0.5 % (0.462 > 0,05), maka variabel (X3) berpengaruh terhadap variabel (Y). Hasil pengujian hipotesis menunjukkan bahwa variabel yang dominan adalah (X2) sebesar 0.227 dengan probabilitas 0.281.Kata kunci: motivasi kepala sekolah, komunikasi, partisipasi orang tua, kinerja guru.